Description of a new Cladolasma (Opiliones: Nemastomatidae: Ortholasmatinae) species from China - Zhang, Chao; Zhang, Feng (Zootaxa, 2013)
The harvestmen genus Cladolasma Suzuki, 1963, previously known only from Japan and Thailand, is here reported from China for the first time. A new species, Cladolasma damingshan sp. nov., is described on the basis of a single male specimen collected from Daming Mountain, Guangxi, China. The new species is distinct from C. parvulum Suzuki, 1963 and C. angka (Schwendinger & Gruber, 1992) in lacking keels around the eyes; and from the known males of C. parvulum in the arrangement of large spines on the penial glans. The finding also represents the first record of Nemastomatidae and Ortholasmatinae for China.